Survey of Herbal Plants In Surrounding of District Siddha Hospital Naruvilikulam, Mannar, Sri Lanka - Sathiyaseelan, V.; Tharshanodayan, N.J.Q. (The International Research & Development Institution, 2021)
Medicinal plant survey was carried out in surrounding of District Siddha Hospital Naruvilikulam, Mannar, Sri Lanka for the express purpose of discovering the distribution of herbs and aware the public to fulfill the medicinal requirement and leads to a healthier life through medicinal plants. Ancestors named the village by using abundant herbs habited on this area. Cordia dicheatoma (Naruvili) plant abundantly distributed in this area. For the reason that, this village named as Naruvilikulam. There are 153 species belonging to 57 families were recorded. Family Fabaceae ranks at the top having 14 medicinal plants species. Around 27 species can be use as Spinaches and 15 species can be use in diabetic management. Habits such as Herbs(59), Shrubs(19), Torn Shrub(09), Creeper(07), Tree(18), Moderate tree(04), Climber(22), Grass(5), Torn climber and Aquatic plant. Arid zone families that are Euphorbiaceae and Cucurbitaceae (09), Laminiaceae (08), Asteraceae and Amaranthaceae (07), Malvaceae, Arecaceae and Solanaceae (06), Acanthaceae and Verbanaceae (05), Zingiberaceae, Apocynaceae and Poaceae (04), Rutaceae, rubiaceae, Araceae and Capparaceae (03) are commonly distributed in this area. Vernonia zeylanica is medicinally important endemic plant species abundantly distributed in this area. The present investigation revealed that the medicinal plants still play a vital role in the primary health care.
Keywords: Naruvilikulam; Fabacea; Arid zone; Spinaches; Plant Survey